2018
DOI: 10.29337/ijops.18
|View full text |Cite
|
Sign up to set email alerts
|

Soleus Muscle Flap Application for Reconstruction of the Middle Third of the Leg

Abstract: Introduction: Lower limb injuries are common in emergency rooms and surgery services. Many are extensive wounds and have complicated and extended treatment. A good option for reconstruction is the use of muscle flaps. Purpose: The aim of this study is to analyze a case series of wounds in the middle third of the leg, using soleus muscle flap for reconstruction and evaluating its effectiveness. Methods: Seven patients with wounds in the middle third of the leg were selected to demonstrate its reconstruction usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…Bortolini and Fraga reported wound infection in one out of six cases. 5 In addition, no necrosis of flaps or suture dehiscence or systemic complications were observed. Hassanpour et al, observed partial flap necrosis in one out of 12 patients in a case series.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Bortolini and Fraga reported wound infection in one out of six cases. 5 In addition, no necrosis of flaps or suture dehiscence or systemic complications were observed. Hassanpour et al, observed partial flap necrosis in one out of 12 patients in a case series.…”
Section: Discussionmentioning
confidence: 89%
“…Due to its constant anatomy and ease of harvest, it is the workhorse flap for soft tissue defects in the middle third of the leg. 5 It is commonly used as a muscle only flap along with split-thickness skin graft (STSG), but it can be modified as a myocutaneous flap or segmental flap. The bony component can be added as required.…”
Section: Introductionmentioning
confidence: 99%